Cholecystokinin-8 protects central cholinergic neurons against fimbria–fornix lesion through the up-regulation of nerve growth factor synthesis - Tirassa, Paola (The National Academy of Sciences, 1999)
In this study, we demonstrate that cholecystokinin-8 (CCK-8) induces an increase in both nerve growth factor (NGF) protein and NGF mRNA in mouse cortex and hippocampus when i.p. injected at physiological doses. By using fimbria–fornix-lesioned mice, we have also demonstrated that repeated CCK-8 i.p. injections result in recovery of lesion-induced NGF deficit in septum and restore the baseline NGF levels in hippocampus and cortex. Parallel to the effects on NGF, CCK-8 increases choline acetyltransferase (Chat) activity in forebrain when injected in unlesioned mice and counteract the septo-hippocampal Chat alterations in fimbria–fornix-lesioned mice. To assess the NGF involvement in the mechanism by which CCK-8 induces brain Chat, NGF antibody was administrated intracerebrally to saline- and CCK-8-injected mice. We observe that pretreatment with NGF antibody causes a marked reduction of NGF and Chat activity in septum and hippocampus of both saline- and CCK-8-injected mice. This evidence indicates that the CCK-8 effects on cholinergic cells are mediated through the synthesis and release of NGF. Taken together, our results suggest that peripheral administration of CCK-8 may represent a potential experimental model for investigating the effects of endogenous NGF up-regulation on diseases associated with altered brain cholinergic functions.